Application of Quasi-Emulsion Solvent Diffusion for Spherical Crystallization of Atorvastatin with HPMC E50 - Indra Indra; Ria Marliana Tika; Winda Trisna Wulandari (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Poor solubility and inadequate flowability of active pharmaceutical ingredients are significant challenges in developing solid oral dosage forms, particularly for BCS Class II drugs such as atorvastatin calcium. This study aimed to improve the micromeritic and dissolution properties of atorvastatin through spherical crystallization using quasi-emulsion solvent diffusion. Methanol was used as a good solvent, dichloromethane as a bridging liquid, water as a poor solvent, and HPMC E50 as a polymeric stabilizer. Spherical agglomerates were prepared and characterized for morphology (SEM); crystallinity (DSC and PXRD); chemical compatibility (FTIR); micromeritic parameters; and dissolution performance. The crystallization process transformed irregular atorvastatin crystals into smooth spherical agglomerates with significantly enhanced flow properties, as evidenced by increased flow rate and improved angle of repose, bulk density, and compressibility index. FTIR analysis confirmed no chemical interaction with HPMC, while PXRD and DSC indicated reduced crystallinity. Dissolution studies showed spherical atorvastatin exhibited superior release, reaching over 80% in 30 minutes, compared with 51% for raw atorvastatin. In conclusion, spherical crystallization effectively improved the physicochemical and micromeritic properties of atorvastatin calcium, offering a promising approach for enhancing its manufacturability and oral bioavailability.